Sulforaphane and Bardoxolone (CDDO)-Induced Inhibition of Aflatoxin B1-Mediated Genotoxicity in Human Lymphocytes: Role of CYP3A4 and CYP1A1 Gene Expression - Safa M. Abdulateef (Journal of Global Pharma Technology, 2016)
Real-time PCR used to investigate the ability of sulforaphane (SFN) and Bardoxolone (CDDO) on inhibition of aflatoxin B1 genotoxicity in Human lymphocytes in vitro. Real time PCR analysis carried out for AFB1 treated lymphocytes with/without SFN and CDDO separately to assess its effects on global transcription through monitoring gene expression variation among genes responsible for AFB1 biotransformation including those involving in AFB1 bio activation like CYP1A1 and CYP3A4, calibrated with B-actin gene. Lymphocytes incubated with 10 and 100ng/ml of AFB1 separately and simultaneously with two different anti-proliferative, anti-inflammatory agents (SFN and CDDO). Protective effect of SFN and CDDO required co-treatments with AFB1. Human lymphocytes incubated with 10 and 100ng/ml AFB1 mixed with 10 and 50µM SFN respectively for 2 hr., on the other hand lymphocytes incubated with 10 and 100ng/ml AFB1 mixed with 10 and 50µ M CDDO respectively for 2hr. CYP1A1 expressed more than CYP3A4 in human lymphocytes; Transcriptional repression for genes involved in AFB1 bio activation was showed after treating with SFN and CDDO. SFN able to inhibit CYP1A1 expression more than CDDO, SFN inhibit CYP1A1 to (~4.32) fold comparing with separately AFB1 treated cells  (P<0.05*).